Core-Collapse Supernova Simulations including Neutrino Interactions from the Virial EOS. Issue Volume 12:Issue S331(2017) (17th October 2017) - O'Connor, Evan; Horowitz, C. J.; Lin, Zidu; Couch, Sean
Abstract: Core-collapse supernova explosions are driven by a central engine that converts a small fraction of the gravitational binding energy released during core collapse to outgoing kinetic energy. The suspected mode for this energy conversion is the neutrino mechanism, where a fraction of the neutrinos emitted from the newly formed protoneutron star are absorbed by and heat the matter behind the supernova shock. Accurate neutrino-matter interaction terms are crucial for simulating these explosions. In this proceedings for IAUS 331, SN 1987A, 30 years later, we explore several corrections to the neutrino-nucleon scattering opacity and demonstrate the effect on the dynamics of the core-collapse supernova central engine via two dimensional neutrino-radiation-hydrodynamics simulations. Our results reveal that the explosion properties are sensitive to corrections to the neutral-current scattering cross section at the 10-20% level, but only for densities at or above 10 12 g cm −3 .